Preparation process of glue for connecting high-strength high-temperature-resistant silicon carbide
The high-strength and high-temperature-resistant silicon carbide connection glue prepared through a multi-step mixing process solves the problems of existing glue failure and poor suspension at high temperatures, and achieves strong connection and high-purity materials for ceramic parts in high-temperature environments. of sintering.
Patent Information
- Application Number
- CN202411491830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The existing glue fails in a high temperature environment above 1000°C and has poor suspension properties, making it not suitable for high-strength high-temperature resistant connections of ceramic parts.
Adopt a preparation process for high -strength high -temperature resistant silicon carbide connection. Through the first, secondary, and three -time mixing steps, amine sulfide water reducing agent, carbon black dispersant, silicon carbide powder, cement enhancer and carboxyl carboxyl Metic cellulose sodium solution, after stirring and vacuum treatment, prepare high -purity and suspended glue.
The glue maintains strength in high-temperature environments, improves the sintering stability and reliability of ceramic joints, and is suitable for bonding primary and secondary sintering ceramic products, extending the service life of the product and improving utilization.
Smart Images

Figure CN119350979A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic manufacturing, and in particular to a preparation process of high-strength and high-temperature resistant silicon carbide connecting glue. Background Art
[0002] The application market of SiC ceramics is extremely broad. In the preparation process of industrial ceramics, parts assembly is sometimes required, and glue is needed at this time. The operating conditions of industrial ceramics have very high strength requirements for glue.
[0003] The current glues are as follows:
[0004] AB glue: It is composed of two parts, one liquid is the glue, and the other liquid is the hardener. The two liquids need to be mixed to harden and be used. Generally speaking, component A is acrylic modified epoxy or epoxy resin, or contains catalysts and other additives, and component B is modified amine or other hardeners, or contains catalysts and other additives. The two liquids can be mixed in a certain proportion to make glue for use.
[0005] 502 glue: It is a single-component instant-curing adhesive synthesized through advanced production technology, mainly based on ethyl α-cyanoacrylate, with the addition of tackifiers, stabilizers, toughening agents, inhibitors, etc. It is applicable to materials such as polyethylene, polypropylene, fluorine-containing and silicon-containing plastics, rubber, soft polyvinyl chloride, etc., which must be specially treated (such as polishing the surface) to obtain good strength, but other materials can be directly bonded.
[0006] Hot melt adhesive: a solid fusible polymer that does not require solvents and does not contain 100% water; it is solid at room temperature, and becomes a liquid that can flow and has a certain viscosity when heated and melted to a certain temperature. The melted EVA hot melt adhesive is light brown or white. EVA hot melt adhesive is composed of basic resin, tackifier, viscosity modifier and antioxidant.
[0007] It can be seen from the existing glue that there are several problems that need to be solved:
[0008] 1. Existing glue can be used at room temperature, but it will fail in high temperature environment above 1000℃. As a ceramic parts adhesive, the commonly used glue is not suitable.
[0009] 2. The ceramic glue currently prepared has poor suspension properties, is difficult to store and use, and is not conducive to production.
[0010] It can be seen from this that a preparation process for high-strength and high-temperature resistant silicon carbide connection glue is urgently needed to solve the above problems. Summary of the invention
[0011] The purpose of the present invention is to provide a preparation process of high-strength and high-temperature resistant silicon carbide connecting glue.
[0012] The scheme of the present invention is:
[0013] A preparation process of high-strength and high-temperature resistant silicon carbide bonding glue comprises the following steps:
[0014] 1) Primary mixing: dissolving 30 to 100 parts by weight of amine sulfonated water reducer and 5 to 10 parts by weight of carbon black dispersant in 4,000 to 6,000 parts by weight of pure water, adding 1,000 to 2,000 parts by weight of carbon black, stirring at a speed of 150 to 160 r / min for 30 to 45 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0015] 2) secondary mixing, slowly adding 13000-20000 parts by weight of silicon carbide powder to the primary treatment mixture, stirring at a speed of 170-180 r / min for 15-25 min, after fully mixing, adding 70-90 parts by weight of cement reinforcing agent, stirring at a speed of 170-180 r / min for 30-45 min to obtain a secondary treatment mixture;
[0016] 3) tertiary mixing, slowly adding 1000-1500 parts by weight of 0.05% sodium carboxymethyl cellulose solution to the secondary treatment mixture, stirring at a speed of 120-140 r / min for 45-50 hours to obtain a mixed solution;
[0017] 4) After the mixed solution is evenly mixed, the mixed solution is poured into a plastic tank and vacuumed for 1 to 2 hours to obtain a high-strength, high-temperature resistant silicon carbide connection glue.
[0018] As a preferred technical solution, the carbon black dispersant in step 1) is a high molecular polymer containing a high-efficiency anchor group.
[0019] As a preferred technical solution, the silicon carbide powder in step 2) is a mixture of coarse silicon carbide powder and fine silicon carbide powder, and the mass ratio of the coarse silicon carbide powder to the fine silicon carbide powder is 2 to 3:1.
[0020] As a preferred technical solution, in the step 2), the cement reinforcing agent accounts for 0.2-0.3% of the total weight.
[0021] As an optimal technical solution, it also includes step 5) use, bonding, drying and sintering, bonding the ceramic dry blank parts according to the drawings, using the high-strength and high-temperature resistant silicon carbide connection glue for bonding, drying in the shade for 5 to 10 minutes, and then drying to obtain a ceramic dry blank sample; loading the coating-sprayed support plate into a sintering furnace, placing the silicon carbide plate thereon for sintering, and burying an appropriate amount of silicon; evacuating and filling with inert gas, heating to 500 to 1200°C at a rate of 1 to 20°C / min, keeping warm for 1 to 6 hours, and then heating to 1400 to 1750°C at a heating rate of 1-10°C / min (the set temperature is proportional to the amount of carbon source added), keeping warm for 1 to 6 hours, and then cooling to room temperature, keeping warm and cooling to room temperature to obtain a ceramic sintered body, and polishing to obtain a high-density ceramic.
[0022] The present invention also discloses a high-strength, high-temperature resistant silicon carbide connection glue, comprising the following raw materials in parts by weight:
[0023] 8000-12000 parts of silicon carbide coarse powder;
[0024] 5000-8000 parts of silicon carbide fine powder;
[0025]
[0026] As a preferred technical solution, the coarse silicon carbide powder and the fine silicon carbide powder are mixed to obtain silicon carbide, and the mass ratio of the carbon black to silicon carbide is 1:18.
[0027] As a preferred technical solution, the mass ratio of the pure water to the amine sulfonated water reducer is 45:1.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. High-purity materials. The preparation method of the present invention can provide high-purity silicon carbide materials with extremely low impurity content, which helps to improve the sintering stability and reliability of the materials. This is particularly important for applications in semiconductors, optoelectronics and other high-tech fields.
[0030] 2. The glue prepared by the raw material ratio of the present invention can enhance the strength of the ceramic connection part after sintering, and is consistent with the material and strength of the ceramic matrix itself, and the sintering method is diverse, and reaction sintering, recrystallization sintering, pressureless sintering, etc. are all applicable. The present invention is suitable for the bonding of ceramic dry blanks, mainly for ceramic primary sintering products; it is also suitable for the bonding of ceramic sintered body parts, mainly for ceramic secondary sintering. On the one hand, it can solve the problem of repairing cracks after ceramic primary sintering, and on the other hand, it can be used for the recycling of ceramic scraps, effectively improving the utilization rate of the product. Starting from the formula, by adjusting the ratio of coarse and fine silicon carbide powder to improve its suspension and density, its mechanical strength is also significantly improved. By adjusting the ratio of carbon black to SiC powder, the strength after sintering is consistent with the ceramic matrix and is not easy to break; by controlling the ratio of sodium carboxymethyl cellulose and pure water, the suspension of the glue is improved, and it is not easy to precipitate, so as to prepare a ceramic-based glue that is conducive to bonding and preservation.
[0031] 3. The raw materials of the present invention do not contain toxic and harmful substances, and the product is applied to the new energy industry. The product has high mechanical strength, improves the qualified rate and service life of the product, increases the utilization rate of the product, and effectively reduces the waste of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a diagram of the product of Example 1 of the present invention used for bonding green pieces;
[0033] Figure 2 This is a picture of the product of Example 1 of the present invention used for grinding the damaged part after sintering;
[0034] Figure 3 This is a diagram of the product of Example 2 of the present invention used for secondary bonding of ceramics after sintering;
[0035] Figure 4 This is a diagram of the product of Example 2 of the present invention being used for secondary sintering after bonding;
[0036] Figure 5 The product of Example 3 of the present invention is used for recrystallization bonding sheet;
[0037] Figure 6 This is a diagram of the product of Example 3 of the present invention used for recrystallization bonding sheet after sintering;
[0038] Figure 7 This is a diagram of the cracks after the product of Example 4 of the present invention is used for ceramic sintering;
[0039] Figure 8 This is a sintering diagram of the product of Example 4 of the present invention after being used for crack repair. DETAILED DESCRIPTION
[0040] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0041] Embodiment 1:
[0042] Glue raw material, 1) primary mixing, dissolving 30 parts by weight of amine sulfonated water reducer and 50 parts by weight of carbon black dispersant in 4000 parts by weight of pure water, adding 1000 parts by weight of carbon black, stirring at a speed of 150 r / min for 30 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0043] 2) Secondary mixing: slowly add 18,000 parts by weight of silicon carbide powder to the uniformly mixed carbon black solution, stir at a speed of 170 r / min for 15 minutes, and after it is fully mixed, add 70 parts by weight of cement reinforcing agent and stir at a speed of 170 r / min for 30 minutes to obtain a secondary treated mixture; the cement reinforcing agent can be 311 concrete reinforcing agent, which is a light yellow transparent liquid with alkali metal silicate as its main component.
[0044] 3) After three mixings, 1000 parts by weight of 0.05% sodium carboxymethyl cellulose solution was slowly added to the mixed solution, and stirred at a speed of 120 r / min for 48 h;
[0045] 4) After 48 hours, the mixed solution is evenly mixed, has good fluidity and a certain viscosity, and then poured into a 500ml plastic jar and vacuumed for 1-2 hours.
[0046] The ratio of silicon carbide to carbon black is 18:1.
[0047] The method for preparing ceramic samples using glue slurry is as follows:
[0048] Bonding: Prepare the ceramic green parts to be bonded, use a brush to apply glue to the joints of the two parts, then connect them on the fixed tooling, fix the position, and then bond them with other parts.
[0049] Drying: Dry the fixed connection blocks in the original position in the shade for 2 hours, then move them to a 50℃ drying room and dry them for 12 hours.
[0050] Sintering: The coated support plate is loaded into the sintering furnace, and the silicon carbide plate is placed on it for sintering, and an appropriate amount of silicon is buried. Vacuum and fill with inert gas, heat to 700℃ at a rate of 15℃ / min and keep it for 3 hours, then heat to 1600℃ at a rate of 4℃ / min, keep it for 4 hours and then cool to room temperature. After cooling to room temperature, the ceramic sintered body is ground and polished to obtain the ceramic product after primary sintering.
[0051] Embodiment 2:
[0052] Glue raw material, 1) primary mixing, dissolving 100 parts by weight of amine sulfonated water reducer and 50 parts by weight of carbon black dispersant in 4500 parts by weight of pure water, adding 1000 parts by weight of carbon black, stirring at a speed of 150 r / min for 30 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0053] 2) Secondary mixing: slowly add 18,000 parts by weight of silicon carbide powder to the uniformly mixed carbon black solution, stir at a speed of 170 r / min for 15 min, and after fully mixing, add 70 parts by weight of cement reinforcing agent and stir at a speed of 170 r / min for 30 min to obtain a secondary treatment mixture;
[0054] 3) After three mixings, 1000 parts by weight of 0.05% sodium carboxymethyl cellulose solution was slowly added to the mixed solution, and stirred at a speed of 120 r / min for 48 h;
[0055] 4) After 48 hours, the mixed solution is evenly mixed, has good fluidity and a certain viscosity, and then poured into a 500ml plastic jar and vacuumed for 1-2 hours.
[0056] The mass ratio of pure water to amine sulfonated water reducer is 45:1.
[0057] The method for preparing ceramic samples using glue slurry is as follows:
[0058] Bonding: Prepare the reaction-sintered ceramic parts that need to be bonded, use a brush to apply glue to the joints of the two parts, then connect them on the fixed tooling, fix the position, and then bond them with other parts.
[0059] Drying: Dry the bonded blocks in the original position in the shade for 4 hours, then move them to a 50℃ drying room and dry them for 24 hours.
[0060] Sintering: The coated support plate is loaded into the sintering furnace, and the silicon carbide plate is placed on it for sintering, and an appropriate amount of silicon is buried. The vacuum is evacuated and filled with inert gas, and the temperature is raised to 700℃ at a rate of 15℃ / min and kept for 3 hours, and then raised to 1500℃ at a rate of 4℃ / min, kept for 4 hours, and then cooled to room temperature. After cooling to room temperature, the ceramic sintered body is ground and polished to obtain the ceramic product after secondary sintering.
[0061] Embodiment 3:
[0062] Preparation of glue raw materials: 1) primary mixing, dissolving 30 parts by weight of amine sulfonated water reducer and 50 parts by weight of carbon black dispersant in 5000 parts by weight of pure water, adding 1000 parts by weight of carbon black, stirring at a speed of 150 r / min for 30 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0063] 2) Secondary mixing: slowly add 18,000 parts by weight of silicon carbide powder to the uniformly mixed carbon black solution, stir at a speed of 170 r / min for 15 min, and after fully mixing, add 70 parts by weight of cement reinforcing agent and stir at a speed of 170 r / min for 30 min to obtain a secondary treatment mixture;
[0064] 3) After three mixings, 1000 parts by weight of 0.05% sodium carboxymethyl cellulose solution was slowly added to the mixed solution, and stirred at a speed of 120 r / min for 48 h;
[0065] 4) After 48 hours, the mixed solution is evenly mixed, has good fluidity and a certain viscosity, and then poured into a 500ml plastic jar and vacuumed for 1-2 hours.
[0066] The mass ratio of coarse silicon carbide powder to fine silicon carbide powder in the silicon carbide powder is 30:10.
[0067] The method for preparing ceramic samples using glue slurry is as follows:
[0068] Bonding: Prepare the recrystallized and sintered ceramic sheets that need to be bonded, use a brush to apply glue to the joints of the two parts, then connect them, and when all the recrystallized sheets are bonded into a plane, fix them in their original position.
[0069] Drying: Leave the fixed connection blocks to dry in the shade for 2 hours, then move them to a 50℃ drying room and dry them for 24 hours.
[0070] Sintering: The coated support plate is loaded into the sintering furnace, and the silicon carbide plate is placed on it for sintering, and an appropriate amount of silicon is buried. Vacuum and fill with inert gas, heat to 700℃ at a rate of 15℃ / min and keep it for 3 hours, then heat to 1600℃ at a rate of 4℃ / min, keep it for 4 hours and then cool to room temperature. After cooling to room temperature, the ceramic sintered body is ground and polished to obtain the target product.
[0071] Embodiment 4:
[0072] Preparation of glue raw materials: 1) primary mixing, dissolving 30 parts by weight of amine sulfonated water reducer and 50 parts by weight of carbon black dispersant in 4000-5000 parts by weight of pure water, adding 1000-2000 parts by weight of carbon black, stirring at a speed of 150r / min for 30 minutes until the carbon black is evenly dispersed, and obtaining a primary treatment mixture;
[0073] 2) Secondary mixing: slowly add 10,000-20,000 parts by weight of silicon carbide powder to the uniformly mixed carbon black solution, stir at a speed of 170 r / min for 15 minutes, and after it is fully mixed, add 70-90 parts by weight of cement reinforcing agent and stir at a speed of 170 r / min for 30 minutes to obtain a secondary treatment mixture;
[0074] 3) After three mixing steps, 1000-1500 parts by weight of 0.05% sodium carboxymethyl cellulose solution was slowly added to the mixed solution, and stirred at a speed of 120 r / min for 48 h;
[0075] 4) After 48 hours, the mixed solution is evenly mixed, has good fluidity and a certain viscosity, and then poured into a 500ml plastic jar and vacuumed for 1-2 hours.
[0076] The raw materials are as follows in parts by weight: 30 parts of amine sulfonated water reducing agent, 50 parts of carbon black dispersant, 1000 parts of carbon black, 18000 parts of silicon carbide powder, 70 parts of cement reinforcing agent, 10 parts of sodium carboxymethyl cellulose, and the cement reinforcing agent accounts for 0.2-0.3% of the total weight.
[0077] The method for preparing ceramic samples using glue slurry is as follows:
[0078] Bonding: Apply glue to the ceramic samples with surface defects after primary reaction sintering, such as cracks and depressions, and wipe off the excess glue with a sponge.
[0079] Drying: Dry the repaired ceramic product in the original position in the shade for 4 hours.
[0080] Sintering: The coated support plate is loaded into the sintering furnace, and the silicon carbide plate is placed on it for sintering, and an appropriate amount of silicon is buried. Vacuum and fill with inert gas, heat to 700℃ at a rate of 15℃ / min and keep it for 3 hours, then heat to 1500℃ at a rate of 4℃ / min, keep it for 4 hours and then cool to room temperature. After cooling to room temperature, the ceramic sintered body is polished to obtain a ceramic product with a smooth surface and no cracks.
[0081] Product Verification
[0082] In order to verify the performance of the product, a universal tester was used to test the three-point bending strength. The products of Example 1, Example 3, and Example 4 are shown in the following table:
[0083] Serial number name Bending strength (four points) (20℃) (Mpa) 1 Example 1 305 2 Example 3 281 3 Example 4 295
[0084] Embodiment 5:
[0085] 1) Primary mixing: dissolving 30 parts by weight of amine sulfonated water reducer and 5 parts by weight of carbon black dispersant in 4000 parts by weight of pure water, adding 1000 parts by weight of carbon black, stirring at a speed of 150 r / min for 30 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0086] 2) secondary mixing, slowly adding 13000 parts by weight of silicon carbide powder to the primary treatment mixture, stirring at a speed of 170 r / min for 15 min, and after fully mixing, adding 70 parts by weight of cement reinforcing agent, stirring at a speed of 170 r / min for 30 min to obtain a secondary treatment mixture;
[0087] 3) tertiary mixing, slowly adding 1000 parts by weight of 0.05% sodium carboxymethyl cellulose solution to the secondary treatment mixture, stirring at a speed of 120 r / min for 48 hours to obtain a mixed solution;
[0088] 4) After 48 hours, the mixed solution is mixed evenly and has good fluidity and a certain viscosity. At this time, the mixed solution is poured into a 500 ml plastic jar and vacuumed for 1 to 2 hours to obtain a high-strength, high-temperature resistant silicon carbide connection glue.
[0089] Embodiment 6:
[0090] 1) Primary mixing: dissolving 100 parts by weight of amine sulfonated water reducer and 50 parts by weight of carbon black dispersant in 6000 parts by weight of pure water, adding 2000 parts by weight of carbon black, stirring at a speed of 150 r / min for 30 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture;
[0091] 2) secondary mixing, slowly adding 20,000 parts by weight of silicon carbide powder to the primary treatment mixture, stirring at a speed of 170 r / min for 15 min, and after fully mixing, adding 90 parts by weight of cement reinforcing agent, stirring at a speed of 170 r / min for 30 min to obtain a secondary treatment mixture;
[0092] 3) tertiary mixing, slowly adding 1500 parts by weight of 0.05% sodium carboxymethyl cellulose solution to the secondary treatment mixture, stirring at a speed of 120 r / min for 48 hours to obtain a mixed solution;
[0093] 4) After 48 hours, the mixed solution is mixed evenly and has good fluidity and a certain viscosity. At this time, the mixed solution is poured into a 500 ml plastic jar and vacuumed for 1 to 2 hours to obtain a high-strength, high-temperature resistant silicon carbide connection glue.
[0094] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A preparation process of high-strength and high-temperature resistant silicon carbide connection glue, characterized in that: The following steps are involved: 1) Primary mixing: dissolving 30 to 100 parts by weight of amine sulfonated water reducer and 5 to 10 parts by weight of carbon black dispersant in 4,000 to 6,000 parts by weight of pure water, adding 1,000 to 2,000 parts by weight of carbon black, stirring at a speed of 150 to 160 r / min for 30 to 45 minutes until the carbon black is evenly dispersed, to obtain a primary treatment mixture; 2) secondary mixing, slowly adding 13000-20000 parts by weight of silicon carbide powder to the primary treatment mixture, stirring at a speed of 170-180 r / min for 15-25 min, after fully mixing, adding 70-90 parts by weight of cement reinforcing agent, stirring at a speed of 170-180 r / min for 30-45 min to obtain a secondary treatment mixture; 3) tertiary mixing, slowly adding 1000-1500 parts by weight of 0.05% sodium carboxymethyl cellulose solution to the secondary treatment mixture, stirring at a speed of 120-140 r / min for 45-50 hours to obtain a mixed solution; 4) After the mixed solution is evenly mixed, the mixed solution is poured into a plastic tank and vacuumed for 1 to 2 hours to obtain a high-strength, high-temperature resistant silicon carbide connection glue.
2. The process for preparing a high-strength, high-temperature resistant silicon carbide connection glue as claimed in claim 1, characterized in that: In the step 1), the carbon black dispersant is a high molecular polymer containing a high-efficiency anchor group.
3. The preparation process of a high-strength, high-temperature resistant silicon carbide connection glue as claimed in claim 1, characterized in that: The silicon carbide powder in the step 2) is a mixture of coarse silicon carbide powder and fine silicon carbide powder, and the mass ratio of the coarse silicon carbide powder to the fine silicon carbide powder is 2 to 3:
1.
4. The process for preparing a high-strength, high-temperature resistant silicon carbide connection glue as claimed in claim 1, characterized in that: In the step 2), the cement reinforcing agent accounts for 0.2-0.3% of the total weight.
5. A high-strength, high-temperature-resistant silicon carbide connecting glue prepared by the preparation process of the high-strength, high-temperature-resistant silicon carbide connecting glue as claimed in any one of claims 1 to 4, characterized in that: The invention comprises the following raw materials in parts by weight:
6. The high-strength and high-temperature-resistant silicon carbide connecting glue prepared by the preparation process of the high-strength and high-temperature-resistant silicon carbide connecting glue as claimed in claim 5 is characterized in that: The coarse silicon carbide powder and the fine silicon carbide powder are mixed to obtain silicon carbide, and the mass ratio of the carbon black to silicon carbide is 1:
18.
7. The high-strength and high-temperature-resistant silicon carbide connecting glue prepared by the preparation process of the high-strength and high-temperature-resistant silicon carbide connecting glue according to claim 1 is characterized in that: The mass ratio of the pure water to the amine sulfonated water reducer is 45:1.